Phase 1 dose-escalation study of S-222611, an oral reversible dual tyrosine kinase inhibitor of EGFR and HER2, in patients with solid tumours. Issue 2 (January 2015) - Spicer, J.; Baird, R.; Suder, A.; Cresti, N.; Corbacho, J. Garcia; Hogarth, L.; Frenkel, E.; Matsumoto, S.; Kawabata, I.; Donaldson, K.; Posner, J.; Sarker, D.; et al.
Abstract Background S-222611 is a reversible inhibitor of EGFR, HER2 and HER4 with preclinical activity in models expressing these proteins. We have performed a Phase 1 study to determine safety, maximum tolerated dose (MTD), pharmacokinetic profile (PK) and efficacy in patients with solid tumours expressing EGFR or HER2. Patients and methods Subjects had advanced tumours not suitable for standard treatment, expressing EGFR or HER2, and/or with amplified HER2. Daily oral doses of S-222611 were escalated from 100 mg to 1600 mg. Full plasma concentration profiles for drug and metabolites were obtained. Results 33 patients received S-222611. It was well tolerated, and the most common toxicities, almost all mild (grade 1 or 2), were diarrhoea, fatigue, rash and nausea. Only two dose-limiting toxicities occurred (diarrhoea and rash), which resolved on interruption. MTD was not reached. Plasma exposure increased with dose up to 800 mg, exceeding levels eliciting pre-clinical responses. The plasma terminal half-life was more than 24 h, supporting once daily dosing. Responses were seen over a wide range of doses in oesophageal, breast and renal tumours, including a complete clinical response in a patient with HER2-positive breast carcinoma previously treated with lapatinib and trastuzumab. Four patients have remained on treatment for more than 12 months. Downregulation of pHER3 was seen in paired tumour biopsies from a responding patient. Conclusions Continuous daily oral S-222611 is well tolerated, modulates oncogenic signalling, and has significant antitumour activity. The recommended Phase 2 dose, based on PK and efficacy, is 800 mg/day.